THE POSITION AND AUTHORITY OF THE CONSTITUIONAL COURT AS ACTORS JUDICIAL POWER - Nawas, Abu (IBLAM LAW REVIEW, 2021)
The paradigm regarding the structure of state institutions underwent drastic changes since the constitutional reform from 1999 to 2002. For various reasons and needs, new state institutions were formed, although some institutions were abolished. One of the institutions formed is the Constitutional Court. The Constitutional Court is designed to be a guard and at the same time an interpreter of the Constitution through its decisions. In carrying out its constitutional duties, the Constitutional Court seeks to realize its institutional vision, namely the establishment of the constitution in the context of realizing the ideals of a state of law and democracy for the sake of a dignified national and state life. This vision becomes a guideline for the Constitutional Court in exercising its judicial power independently and responsibly in accordance with the constitutional mandate. The Constitutional Court  work since its presence has been considered quite significant, especially in its contribution to maintaining the law and developing democracy